From linear to systemic: an integrated design solution for sustainable household consumption in Iceland - Hua, M; Huang, S; Childs, P (Design Society, 2016)
Sustainable consumption patterns are one of the key driving forces to achieve sustainable development. However, studies in design research tend to draw on the existing system of production and consumption with its inherent linear processes, which are often wasteful and polluting. Here we report on a project for a Nordic family in Iceland which had the dual aims of introducing a new holistic research method into the consumption research sector and investigating ways to optimize the family’s use of resources from a Systemic Design (SD) perspective. Using SD theory, we redesigned the material and energy flows run in the house and optimized the relationships between its system elements. These programmed changes improved the efficiency of the current system and provided opportunities for subsequent design innovation.